Physical Condition Characteristics of Junior Rafting Athletes at FAJI Purbalingga - Setiadi, Khairul Mada; Islam, Syahrizal (Pedagogy and Psychology of Sport, 2026)
Background. Physical fitness is a crucial component in supporting athlete performance in various sports, including whitewater rafting. This sport demands complex physical abilities, including aerobic endurance, upper-body strength, leg explosiveness, and core stability to navigate dynamic, challenging river currents. Aim. This study aims to determine the physical condition characteristics of junior rafting athletes in Purbalingga and to analyze differences in physical condition test results by competition category. Material and Methods. This study used an observational, quantitative approach. The subjects consisted of 68 junior rafting athletes aged 15–18 years from a rafting club in Purbalingga. Physical condition measurements included the Multi-Stage Fitness Test (MFT), push-up test, pull-up test, vertical jump test, and plank test. Data analysis was performed using descriptive statistics and the Mann–Whitney and Kruskal–Wallis tests, with a significance level of p < 0.05, in SPSS version 24. Results. The study found that only height variables showed significant differences between male and female athletes (p < 0.05), while age, weight, and BMI did not. In addition, there were no significant differences in all components of physical condition between rafting competition categories (p > 0.05). In general, most athletes were in the Good (43%) and Fair (31%) categories. Conclusions. The physical condition of junior whitewater rafting athletes in Purbalingga is generally good. The training program implemented has improved the athletes' basic physical condition, but more targeted training is still needed to optimize performance.